Analysis of reaction cross-section production in neutron induced fission reactions on uranium isotope using computer code COMPLET. (September 2018) - Asres, Yihunie Hibstie; Mathuthu, Manny; Birhane, Marelgn Derso
Abstract: This study provides current evidence about cross-section production processes in the theoretical and experimental results of neutron induced reaction of uranium isotope on projectile energy range of 1–100 MeV in order to improve the reliability of nuclear stimulation. In such fission reactions of 235 U within nuclear reactors, much amount of energy would be released as a product that able to satisfy the needs of energy to the world wide without polluting processes as compared to other sources. The main objective of this work is to transform a related knowledge in the neutron-induced fission reactions on 235 U through describing, analyzing and interpreting the theoretical results of the cross sections obtained from computer code COMPLET by comparing with the experimental data obtained from EXFOR. The cross section value of 235 U(n, 2n) 234 U, 235 U(n, 3n) 233 U, 235 U(n, γ ) 236 U, 235 U(n, f) are obtained using computer code COMPLET and the corresponding experimental values were browsed by EXFOR, IAEA. The theoretical results are compared with the experimental data taken from EXFOR Data Bank. Computer code COMPLET has been used for the analysis with the same set of input parameters and the graphs were plotted by the help of spreadsheet & Origin-8 software. The quantification of uncertainties stemming from both experimental data and computer code calculation plays a significant role in the final evaluated results. The calculated results for total cross sections were compared with the experimental data taken from EXFOR in the literature, and good agreement was found between the experimental and theoretical data. This comparison of the calculated data was analyzed and interpreted with tabulation and graphical descriptions, and the results were briefly discussed within the text of this research work. Highlights: Theoretical calculation of reaction cross-section using Computer code COMPLET. Experimental data base verifications using EXFOR, nuclear reaction cross-section data center. Comparison of the calculated reaction cross-section values with the experimental data.